2018
DOI: 10.1016/j.cej.2017.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Sorptive removal of phenolic endocrine disruptors by functionalized biochar: Competitive interaction mechanism, removal efficacy and application in wastewater

Abstract: Sorptive removal of six phenolic endocrine disrupting chemicals (EDCs) estrone (E1), 17βestradiol (E2), estriol (E3), 17α-ethynylestradiol (EE2), bisphenol A (BPA) and 4-tertbutylphenol (4tBP) by functionalized biochar (fBC) through competitive interactions was investigated. EDC sorption was pH dependent with the maximum sorption at pH 3.0-3.5 due to hydrogen bonds and π-π interactions as the principal sorptive mechanism. Sorption isotherm of the EDCs was fitted to the Langmuir model. Sorption capacities and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…The subsequent increase in pH resulted in a further decrease in the adsorption capacity of BC to bisphenol A. This is because the π-π electron donor-acceptor interaction (EDA) and hydrogen bonding between BC and BPA is weakened when the pH of the solution is greater than the acid dissociation constant of BPA [61]. The adsorption capacity of bisphenol A by MBC increased at first and then decreased with the increase of pH, and the maximum adsorption capacity occurred at pH = 6.…”
Section: Effects Of Initial Bpa Concentration and Temperaturementioning
confidence: 99%
“…The subsequent increase in pH resulted in a further decrease in the adsorption capacity of BC to bisphenol A. This is because the π-π electron donor-acceptor interaction (EDA) and hydrogen bonding between BC and BPA is weakened when the pH of the solution is greater than the acid dissociation constant of BPA [61]. The adsorption capacity of bisphenol A by MBC increased at first and then decreased with the increase of pH, and the maximum adsorption capacity occurred at pH = 6.…”
Section: Effects Of Initial Bpa Concentration and Temperaturementioning
confidence: 99%
“…Therefore, repulsive interactions did not occur, which could justify the higher adsorption capacity of carbamazepine than for sulfamethoxazole. The adsorption of five endocrine disruptors, namely estrone (E1), 17β-estradiol (E2), estriol (E3), 17α-ethynylestradiol (EE2) and bisphenol A (BPA), on an activated carbon from Eucalyptus globulus wood activated with H 3 PO 4 was analyzed by Ahmed et al [220]. The authors concluded that π-π electron donor-acceptor interactions were responsible of adsorption.…”
Section: Contaminantmentioning
confidence: 99%
“…Yin [ 4 ] has reported that the activated magnetic biochars (AMBCs) could be used as an effective adsorbent for removing E2 (the highest capacity 153.2 mg·g −1 ) by one-step synthesis. Mohammad [ 14 ] has researched that functionalized biochar with enhanced functional groups, specific surface area, and meso- and macro-pores prepared could be successfully applied for the removal of six phenolic EDCs. Biochar has been universally employed as a functional material for adsorption known for its large specific surface area, high porosity, and high physicochemical stability [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%